Peran Perpustakaan dalam Pelestarian Budaya Lokal di Dinas Perpustakaan dan Kearsipan Kabupaten Pakpak Bharat - Manik, Vera Sriyuni; Siregar, Yusra Dewi (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
Indonesia is a country of cultural diversity from Sabang to Merauke. The role of libraries has great significance as an effort to preserve and maintain these cultural values. Libraries as information centers also have a function as cultural preservation. However, besides that we need to explore what role the library plays in preserving local culture. This research aims to find out how the role of libraries in preserving local culture. This research uses qualitative methods with direct observation and interviews with librarians. Libraries have a very important role in preserving local culture in Pakpak Bharat Regency. Pakpak people in general also have a greeting pattern or pertuturen where someone will call their relatives with a distinctive and polite greeting and have a function for each term of greeting. Through its programs, the library is able to become an effective agent in documenting, promoting, and introducing cultural heritage to the community.